(untitled) (Agricultural Engineering, 2016)
The objective of the paper is to determine the optimal geometric parameters of the windshield device limiting the spray drift by wind in herbicides spraying. Tests were carried out with the use of the planning methods of experiments and statistical methods of processing of the obtained results. The result of the research consisted in obtaining structural parameters of the windshield made in the shape of gratings with rectangular boards. It was found out that this device may be used at the wind speed exceeding agrotechnological sizes. The research results will be used in the work on devices protecting against wind at a precise herbicides spraying.